The medium is terrorism: Transformation of the about to die trope in Dabiq. Issue 2 (4th March 2019) - Winkler, Carol K.; El Damanhoury, Kareem; Dicker, Aaron; Lemieux, Anthony F.
Abstract: Daesh's ability to successfully recruit foreign fighters from more than one hundred countries worldwide raises the importance of understanding the group's strategic media campaign. Recognizing that visual images, in particular, often increase viewers' attention, recall, and emotional response, this study of Daesh's official magazine, Dabiq, moves beyond earlier studies primarily focused on the magazine's textual content to analyze the group's visual communication strategy. This study's content analysis of the 1, 144 images appearing in the magazine's first twelve issues reveals how Dabiq has relied extensively on a historic American media trope, the about to die image, to bolster image recirculation over time. This essay examines both the form and content of Dabiq 's use of three about to die image types as they have evolved across the twelve issues. Rather than seek to win the "hearts and minds" of the Muslim public, Dabiq 's use of about to die images transforms the online medium into terrorism in ways that have lasting implications for the global culture.